Physiological response of broilers raised under simulated conditions of heat waves - Malagoli De Mello, J. L. [UNESP]; Manente Boiago, M.; Giampietro-Ganeco, A. [UNESP]; Piatto Berton, M. [UNESP]; Alves de Souza, R. [UNESP]; Borba Ferrari, F. [UNESP]; Alves de Souza, P. [UNESP]; Borba, H. [UNESP] (Cordoba University Press (UCOPress), 2018)
To evaluate the influence of heat stress for up to 72 hours, and the possible cumulative effect of heat stress on the physiological responses of broilers raised under simulated conditions of heat waves, 500 male Cobb broilers were raised in two climatic chambers equipped with heating and cooling mechanisms, for up to 45 days. Half of the birds were raised in thermal comfort and the remainder broilers were submitted to heat waves (32 °C ± 0.5 °C for up to 72 hours) in three ages (starting at 21, 35 and 42 days of age). In the beginning of each heat wave simulation and after 24, 48 and 72 hours of exposure to heat stress, physiological parameters as rectal temperature and respiratory frequency were measured, and blood samples were collected for determining hormonal levels (T3 and T4) and hematocrit. The increase of the birds’ respiratory frequency was verified after 24 hours of exposure to high temperatures in three simulated heat waves. During the third heat wave there was no variation of the rectal temperature. The environmental temperature did not influence the hematocrit value, and T3 and T4 thyroid hormone levels. Submit birds to periods of intermittent acute heat stress, like during the simulation of heat waves, influences the broilers’ respiratory frequency and rectal temperature, showing the consequent effect of heat stress on the birds’ metabolism and body thermal balance. Heat waves doesn’t affect the secretion of triiodothyronine and thyroxine, and the percentage of red blood cells.
Respostas de frangos de corte criados sob estresse por calor
Keywords: Ambience; Heat stress; Thermoneutrality; Thermoregulation